Release characterization and biological effect of Glass Ionomer Functionalized with two different chlorohexidine derivatives: an in vitro study - Shaimaa M. Abdellah HASSAN; Mohamed M. KANDIL; Dina El-REFAIE (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT Objective: To evaluate the effect of adding two different chlorohexidine derivatives; chlorhexidine hexametaphosphate and chlorhexidine digluconate to glass ionomer at three different concentrations (0.25%, 0.75%and 1.5%) regarding the antibacterial effect, chlorhexidine release and fluoride release. Methods: A total of 405 specimens were prepared and tested after 7 days, 3 months and 6 months of storage in distilled water (n=5).For testing antibacterial effect, chlorhexidine release and fluoride release, the mix was packed in a ready-made Split Teflon molds to obtain disc-shaped specimen with dimensions 10 mm in diameter and 2 mm thickness according to ISO standardizations. One-way ANOVA and One-way repeated measure ANOVA test were used for statistical analysis of data. Results: The incorporation of chlorhexidine into ChemFil Superior glass ionomer cement in both derivatives has high significance ability to provide a long-term antimicrobial effect on Streptococcus mutans and Lactobacillius acidophilus. The chlorhexidine release was increased by adding chlorhexidine in both derivatives to GIC than the unmodified Glass-ionomer cement for study duration. However, the fluoride release was decreased in the modified specimens than the original one. Conclusion: Addition of chlorhexidine enhanced the antibacterial effect of the glass ionomer and chlorhexidine release. However, fluoride release was reduced than original